INTELLECTUAL POTENTIAL OF HUMAN CAPITAL (European Journal of Economics, Finance and Business Development, 2025)
Reforms are being implemented in Uzbekistan to develop the rule of law and human capital, to build a fair and strong civil society, and to further improve the living conditions of the population. In this article, the development of human capital - intellectual ability is one of the urgent issues of today and the need to strengthen its regulatory and legal foundations.